EFFECTS OF DRINKING WATER QUALITY ON EPIGENETIC FACTORS: A MOLECULAR–HYGIENIC INVESTIGATION (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Drinking water quality plays a crucial yet often underestimated role in influencing epigenetic mechanisms that regulate gene expression and determine long-term health outcomes in human populations. As environmental exposures increasingly intersect with molecular biology, a growing body of evidence suggests that contaminants such as heavy metals, disinfection by-products, endocrine-disrupting chemicals, microbial metabolites, and nano-sized particles present in drinking water can induce stable yet reversible epigenetic alterations involving DNA methylation, histone modifications, non-coding RNA dynamics, chromatin remodeling, and transgenerational regulatory changes.